THE RELATIONSHIPS OF RISKS AND INCOMES IN FARMING IN WETLAND AND DRYLAND OF NORTH LOMBOK, INDONESIA - T Sjah; I Budastra; I G L P Tanaya; Wuryantoro Wuryantoro; N L S Supartiningsih; S Maryati (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
Risk is a constant threat to businesses, including to farms in North Lombok, Indonesia. This paper examines the relationships between risks of farming and incomes generated by the selected farms. Data related to farm risks and incomes were collected from samples of farmers in wetland and dryland in North Lombok Indonesia, through series of face-to-face interviews on the farms or farmers houses, guided by a semi-structured questionnaire. Quantitative analyses were carried out on farm risk levels and income, followed by descriptive comparative on examination of the relationships between the two main variables of this paper. Results of analyses revealed that incomes from farming crops in North Lombok were not obviously related to the risks associated with the crop production and market. However, agricultural producers have selected crops for their suitability to the land (soil) and local climate, by which farming risks were reduced or eliminated, for sustaining farming activities, and expecting high farm income. Since crops have been suitable to the land climate, as well as to the acceptable risk, then agricultural production is continued and income is generated for the farmers.